FINANCIAL MECHANISM OF STATE REGULATION OF THE ELECTION PROCESS - Dmytrenko , H. (Theory and Practice of Public Administration, 2021)
The financial mechanism of state regulation of the electoral process is studied using the methods of public administration science, as a subject of practical activities of public administration and administration.The concept of “financial mechanism” is analyzed. Its place, role and essence in the election process are clarified. It is noted that the conduct of competitive elections implies that the participants in the election race have the funds to conduct the election campaign and carry out current activities.The experience of European countries on state funding of political parties is considered.The rules for financing political parties and election campaigns should be based on the following principles: a reasonable balance between public and private funding, fair criteria for the distribution of state party contributions, strict rules on private donations, the threshold of campaign expenses, full transparency of accounts, independent audit body and substantive sanctions for parties and candidates who violate the rules. These principles are set out in more detail in the following pages.